CRISPR/Cas13-Based Approaches for Ultrasensitive and Specific Detection of microRNAs - Javier T. Granados-Riveron (Cells, 2021)
MicroRNAs (miRNAs) have a prominent role in virtually every aspect of cell biology. Due to the small size of mature miRNAs, the high degree of similarity between miRNA family members, and the low abundance of miRNAs in body fluids, miRNA expression profiling is technically challenging. Biosensors based on electrochemical detection for nucleic acids are a novel category of inexpensive and very sensitive diagnostic tools. On the other hand, after recognizing the target sequence, specific CRISPR-associated proteins, including orthologues of Cas12, Cas13, and Cas14, exhibit collateral nonspecific catalytic activities that can be employed for specific and ultrasensitive nucleic acid detection from clinically relevant samples. Recently, several platforms have been developed, connecting the benefits of enzyme-assisted signal amplification and enzyme-free amplification biosensing technologies with CRISPR-based approaches for miRNA detection. Together, they provide high sensitivity, precision, and fewer limitations in diagnosis through efficient sensors at a low cost and a simple miniaturized readout. This review provides an overview of several CRISPR-based biosensing platforms that have been developed and successfully applied for ultrasensitive and specific miRNA detection.